Commitment of Madrasah Heads in Improving State Tsanawiyah Madrasah Services in the Kepulauan Riau - Siti Mariyah; Ahmad Syukri; Badarussyamsi (PT. PENERBIT TIGA MUTIARA, 2024)
The purpose of this research is to determine the form of educational services that have been implemented by the Head of the State Madrasah Tsanawiyah in the Riau Islands, and the commitment of the Head of the Madrasah in improving the educational services of the State Madrasah Tsanawiyah in the Riau Islands. This research is a type of field research with a descriptive qualitative approach. The subject of this research covers aspects related to the commitment of madrasa heads in organizing the cultural governance of educational services at the State Tsanawiyah Madrasah in the Riau Islands, which consists of the leadership of the MTsN Riau Islands, as well as teachers and other educational staff. The data collection techniques are through documentation, behavioral observation, or interviews with participants. The data was then analyzed through three components, namely data reduction, data presentation and conclusion drawing. The results of this research show that madrasa heads must be committed to taking real action to improve the quality of education at State MTs in the Riau Islands. Concrete steps that can be taken are to initiate teacher training programs, update the curriculum to reflect the latest developments, and strive for (tangible) facilities that are comfortable and conducive to learning. Madrasah heads must also try to always be open to input from all parties involved in the educational process.